THE CONCEPTUAL FRAMEWORK TO INTEGRATE SUSTAINABILITY IN URBAN REGENERATION INITIATIVES - Nik Hashim, Nik Hazwani; Alias , Anuar; Md. Dali, Melasutra (International Journal of Property Sciences (E-ISSN: 2229-8568), 2022)
Urban regeneration has become an essential spatial strategy to resolve urban decay issues in many countries and regions which is in line with the ‘2030 Agenda for Sustainable Development to build sustainable cities and communities worldwide. Although urban regeneration is the desired solution for deprived cities, not all are successful in following the sustainable development path as more emphasis is on economic objectives over the environment and social sustainability. Thus, this study presents the conceptual framework that integrates sustainable development aspirations in the urban regeneration practice as the way forward. A qualitative method (content analysis approach) is adopted in this study by reviewing current and past studies on sustainable urban regeneration, using Mendeley as the search engine and ATLAS.ti for analysing. Findings from the literature review identified fundamental criteria and indicators of sustainable urban regeneration according to the three dimensions of sustainable development. A strategic approach to achieving sustainable urban regeneration is also identified which indicates that planning and social sub-systems are the crucial components or the enablers that integrate sustainability in urban regeneration initiatives. This study concluded that urban regeneration could be the solution to resolve urban decay and build sustainable cities if the town planning and social sub-system are incorporated appropriately within the sustainable urban regeneration framework.